Microbial and Host Factors That Affect Bacterial Invasion of the Gingiva. (August 2020) - Ji, S.; Choi, Y.
Periodontitis is a chronic inflammation of the periodontium caused by the loss of homeostasis between subgingival biofilms and susceptible hosts. Bacterial invasion into the gingival tissue and persistent infection are major events that lead to chronic inflammation. The intratissue bacterial communities are as complex as the subgingival biofilms and can also form biofilm-like structures, which will serve as a reservoir for local and systemic infections. The epithelium forms physical, chemical, and immunological barriers against invading microbes. Nevertheless, many bacterial species can invade the gingival epithelium through transcellular and paracellular pathways. In addition, both genetic and environmental factors of the hosts can affect epithelial barrier functions and thus bacterial invasion of the gingiva. In this review, current evidence for the bacterial invasion of the gingival tissue in periodontitis has been summarized, and the microbial and host factors that determine bacterial invasion of the gingiva have been reviewed.